2023
DOI: 10.3390/ijms24021628
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Highlights of miRNAs in Asthma: Biomarkers for Diagnosis and Treatment

Abstract: Asthma is a heterogeneous inflammatory disease of the airways that causes breathing difficulties, episodes of cough and wheezing, and in more severe cases can greatly diminish quality of life. Epigenetic regulation, including post-transcriptional mediation of microRNAs (miRNAs), is one of the mechanisms behind the development of the range of asthma phenotypes and endotypes. As in every other immune-mediated disease, miRNAs regulate the behavior of cells that shape the airway structure as well as those in charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Currently, many publications show miRNAs as potential asthma diagnostic biomarkers [13,[15][16][17]. Few studies have also drawn attention to the relationship between miRNAs and a particular therapeutic regimen.…”
Section: Mirnas and Individual Groups Of Drugs Used In Asthma (Glucoc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many publications show miRNAs as potential asthma diagnostic biomarkers [13,[15][16][17]. Few studies have also drawn attention to the relationship between miRNAs and a particular therapeutic regimen.…”
Section: Mirnas and Individual Groups Of Drugs Used In Asthma (Glucoc...mentioning
confidence: 99%
“…Their broad impact on the processes involved in the pathogenesis of asthma has been confirmed (including the proliferation of smooth muscle cells, increased mucus production, collagen, and overactivity of the respiratory tract) [12]. These are small, non-coding RNA biomolecules, 18-25 nucleotides long, and regulate gene expression at the posttranscriptional level by binding to the target mRNA (messenger RNA) [13]. Due to their role in multiple cellular processes, such as inflammatory and immunomodulatory processes, they are an important future target of therapeutic activities leading to increased and improved sensitivity to steroid therapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mir-21, mir-223, and Let-7a were selected for their role in the development and pathogenesis of different forms of asthma. Recent asthma-specific findings show their role as significant contributor to the asthma process [20][21][22]. Further studies on more miRNAs will be required.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Despite extensive investigations into the role of miRNAs in the development of asthma [21][22][23], to date, studies on the functioning of exosomal miRNAs in this disease are lacking [24]. Based on the above, we therefore believe that alterations of intracellular miRNAs and circulating miRNAs can probably be implicated in the etiopathogenesis of asthma and of severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the accumulated evidence showing that obesity is a risk factor for developing severe asthma, the possibility that this effect could be mediated, at least in part, via modification of the expression of genes associated with asthma severity has been poorly studied. Some studies analyzed microRNA expression and found higher levels of hsa-miR-155-5p and 223-5p in moderate asthmatics and obese subjects compared to healthy controls [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%